Management of leaf blight of chrysanthemum caused by Alternaria alternata in Northern Karnataka - YASHASWINI SHARMA, M.R. RAVIKUMAR*, K.B. YADAHALLI AND (Indian Phytopathology, 2016)
Chrysanthemum (Chrysanthemum morifolium Ramat.) is an important commercial flower crop used mainly as loose flower in domestic market and as a popular cut flower in the world market. The plant is being affected by leaf blight caused Alternaria alternata (Fries) Keissler, a serious disease directly affecting the flower yield. Hence a study on field screening of chrysanthemum against leaf blight was taken up during 2014-2015 at farmers field with six chemicals viz, Â Tebuconazole @0.1%, Propiconazole @ 0.1%, Difenconazole @ 0.1%, Hexaconazole @ 0.1% , Chlorothalonil @ 0.2% and Mancozeb @ 0.2%. Four sprays were taken up at 10 days interval with each fungicide. Among the different treatments, the plants sprayed with Tebuconazole, Propiconazole and Difenconazole @ 0.1% were found effective in controlling the leaf blight disease and recorded lowest disease index (5.12 per cent, 5.38 per cent, 6.75 per cent disease index, respectively) when compared to control (57.26 per cent disease index) after the forth spray. Highest yield (72.55 q/ha) was recorded with Tebuconazole treated plants followed by Propiconazole treatment (70.25 q/ha) and Difenconazole treatment (69.30 q/ha) and the least yield (51.35 q/ha) was recorded with untreated control.